Reliability and validity of the weight status and dietary intake measures in the COMPASS questionnaire: are the self-reported measures of body mass index (BMI) and Canada’s food guide servings robust? - Leatherdale, Scott T (BioMed Central, 2013)
BACKGROUND: The COMPASS study is designed to follow a cohort of ~30,000 grade 9 to 12 students attending ~60 secondary schools for four years to understand how changes in school characteristics (policies, programs, built environment) are associated with changes in youth health behaviours. Since the student-level questionnaire for COMPASS (C(q)) is designed to facilitate multiple large-scale school-based data collections using passive consent procedures, the C(q) is only comprised of self-reported measures. The present study assesses the 1-week (1wk) test-retest reliability and the concurrent validity of the C(q) measures for weight status and dietary intake. METHODS: Validation study data were collected from 178 grade 9 students in Ontario (Canada). At time 1 (T(1)), participants completed the C(q) and daily recoding of their dietary intake using the web-based eaTracker tool. After one week, (T(2)), students completed the C(q) again, participants submitted their daily eaTracker logs and staff measured their height and weight. Test-retest reliability of the self-reported (SR) weight status and dietary intake measures at T(1) and T(2), and the concurrent validity of the objectively measured and SR weight status and dietary intake measures at T(2) were examined using intraclass correlation coefficients (ICC). RESULTS: Test-retest reliability for SR height (ICC 0.96), weight (ICC 0.99), and BMI (ICC 0.95) are considered substantial. The concurrent validity for SR height (ICC 0.88), weight (ICC 0.95), and BMI (ICC 0.84) are also considered substantial. The test-retest reliability for SR dietary intake for fruits and vegetables (ICC 0.68) and milk and alternatives (ICC 0.69) are considered moderate, whereas meat and alternatives (ICC 0.41), and grain products (ICC 0.56) are considered fair. The concurrent validity for SR dietary intake identified that fruits and vegetables (ICC 0.53), milk and alternatives (ICC 0.60), and grain products (ICC 0.41) are considered fair, whereas meat and alternatives (ICC 0.34) was considered slight. CONCLUSIONS: While the test-retest reliability of the measures used in this study were all high, the concurrent validity of the measures was considered acceptable. The results support the use of the self-reported COMPASS weight status and dietary intake measures for use in research where objective measures are not possible.